Torque balancing control in ignition event based scale for multi-cylinder SI engines. (18th December 2008) - Li, Po; Liu, Kaipei; Shen, Tielong; Kako, Junichi
In this paper, the torque balancing problem for multi-cylinder SI engines is focused on. The deviation in average torque generation of sections with equal crank angle interval according to ignition event is introduced as index for balancing and an estimation method for this index from engine speed measurement is proposed based on crank shaft dynamics in crank angle domain. According to the coupling characteristic in torque generation between cylinders, a simple 2nd order ARMA model is established to describe the dynamics from spark ignition to the index. Based on this model, model predictive control technique is used in regulation. Finally, the validity of the proposed approach is demonstrated by simulation performed on a six-cylinder engine simulator with physical background.